A Study on Examining the Impact of AI Tools on Students’ Study Habits and Academic Success (Don Bosco Institute of Technology Delhi Journal of Research, 2025)
This study examines the role of AI tools in shaping students’ study habits and  academic outcomes, focusing on their integration into educational routines. A  mixed-methods approach was employed, combining survey data and qualitative  feedback from 141 students across diverse demographics and disciplines. Key  findings reveal a moderate level of AI usage, with 57% of students utilizing  AI tools for 26-50% of their study time. AI tools were reported to enhance  efficiency, motivation, and GPA while reducing study hours. Despite these  benefits, challenges such as over-reliance and integration with traditional  methods were identified. The study underscores the importance of a balanced  approach to AI adoption, advocating for its role as a complementary tool  alongside conventional study practices. Actionable recommendations include  promoting responsible usage, addressing privacy concerns, and fostering  inclusivity to maximize AI’s educational potential.
Keywords: Artificial Intelligence; Education; Study Habits; Academic Performance; Personalized Learning and Adaptive Learning Tools